Dispersion-strengthened aluminum prepared by mechanical alloying - Besterci, M. (Michal) (Cambridge International Science Pub., 1999)
In the book, the author describes the theoretical and technological fundamentals of mechanical alloying the AI-C system. Special attention is given to material characteristics, the kinetics and mechanism of mechanical alloying, methods of mixture compaction and heat treatment of compacted parts. Models of dispersoid spatial arrangement, dispersoid evaluation and optimisation and experimental possibilities are discussed. The interpretation of the static and dynamic mechanical properties, especially strength and ductility properties at 20 C, mechanical properties at elevated temperatures are discussed, with emphasis on the effect of interface, superplasticity, creep and creep-fatigue characteristics. -- Provided by publisher.